Epidemiology of Anterior Cruciate Ligament Tears in the National Football League - Palmieri-Smith, R. M.; Mack, C. D.; Brophy, R. H.; Owens, B. D.; Herzog, M. M.; Beynnon, B. D.; Spindler, K. P.; Wojtys, E. M. (The American Journal of Sports Medicine, 2021)
Background: Anterior cruciate ligament (ACL) tears are common in contact athletics and have a significant effect on the athletic performance and well-being of affected players. The prevalence, timing, and characteristics of ACL tears in National Football League (NFL) athletes are lacking.